MEMS-based low-cost and open-source accelerograph for earthquake strong-motion. (1st March 2021) - Bravo-Haro, M.A.; Ding, X.; Elghazouli, A.Y.
Highlights: Development and calibration of an open-source low-cost strong motion sensor. Full characterisation of the sensor is provided. Detailed static and dynamic tests are undertaken for calibration purposes. Standard and statistical tests to assess the sensor performance are presented. Novel sensor can be deployed as an accelerograph for seismic monitoring of structures. Abstract: This paper describes a sensing technique that has been entirely built from off-the-shelf electronic components, with the aim of providing its construction and programming guidelines as an open-source platform which can be continuously updated. The assessments carried out in this investigation indicate that the proposed sensor is suitable for deployment as an accelerograph for seismic monitoring of structural systems. The results show low levels of self- noise, considering the nature of the MEMS analogue accelerometer embedded in the sensor. The amplitude transfer functions exhibit a flat behaviour for the full range of frequencies tested, whose boundaries were limited by the installed capacity within the laboratory. However, this flat behaviour is expected to be coherent up to the resonant frequency of the MEMS accelerometer, whose absolute value is much higher than the bandwidth of frequencies of interest for seismologists and structural earthquake engineers. The clipping tests demonstrate a high linearity of the amplitude transfer function from low acceleration levels up to the vicinity of the maximum nominal recordable acceleration of ±3 g at which a typical roll-off is observed. Under long-time operations, the sensor produces a robust performance, maintaining a steady pace of sampling. The performance of the sensor was finally tested considering non-stationary signals, using a linear shake table to reproduce a wide ensemble of strong-motion recordings from actual earthquakes. Intensity measures of strong-motion commonly used in earthquake engineering were appraised, such as horizontal spectral acceleration, Arias Intensity, and transient peaks of response.